Peran Taman Bacaan Masyarakat Mata Aksara dalam menumbuhkan minat baca pada masyarakat - Dwiyantoro Dwiyantoro (Jurnal Kajian Informasi dan Perpustakaan, 2019)
People’s reading interest in Indonesia is 0.001% and is ranked third from the bottom, lagging far behind other countries that have an average percentage of 0.45% -0.62%. While for the percentage of reading interest based on province, Yogyakarta ranks third with a percentage of 91.00%. Based on these conditions, indeed, it requires a provider of information which is easy to access to increase reading interest. One of the information providers is Taman Bacaan Masyarakat (TBM)/Community Reading Park. To find out more about this, obviously, research needs to be conducted relating to the role of TBM in supporting information dissemination among the community. The research location was Mata Aksara TBM. The purpose of this study was to determine the role of Mata Aksara TBM for the community. This study used a qualitative approach through descriptive research methods, with Mata Aksara TBM, Yogyakarta as the study subject. The data collection technique used was observation and interviews. Results of the study indicated that Mata Aksara TBM acted as a place of learning and play, as a place of learning and practice, as a place of recreation and education, and as a place to preserve culture. The conclusion from this study is that the Community Reading Park is beneficial in empowering reading interest, especially among children, and has a positive impact on the community in the TBM environment in advancing the agricultural and livestock sectors of the society around the TBM.